2013
DOI: 10.3389/fpsyg.2013.00639
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on explicit and implicit memory

Abstract: It is well-documented that explicit memory (e.g., recognition) declines with age. In contrast, many argue that implicit memory (e.g., priming) is preserved in healthy aging. For example, priming on tasks such as perceptual identification is often not statistically different in groups of young and older adults. Such observations are commonly taken as evidence for distinct explicit and implicit learning/memory systems. In this article we discuss several lines of evidence that challenge this view. We describe how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 67 publications
(111 reference statements)
2
39
0
2
Order By: Relevance
“…In contrast, we should not expect an age-related decline for the past dimension of the IAMI following the theoretical position that involuntary autobiographical memories form a basic mode of remembering that requires less executive processes and therefore may show less age-related impairments (Berntsen, 2009; 2012; Hall et al, 2014). This would also be consistent with research suggesting that older individuals show less decrement in performance on memory tasks that are assumed to involve less cognitive effort, although findings are mixed (see Ward, Berry & Schanks, 2013, for review and discussion). Study 4 was undertaken to examine this issue.…”
Section: Studysupporting
confidence: 85%
“…In contrast, we should not expect an age-related decline for the past dimension of the IAMI following the theoretical position that involuntary autobiographical memories form a basic mode of remembering that requires less executive processes and therefore may show less age-related impairments (Berntsen, 2009; 2012; Hall et al, 2014). This would also be consistent with research suggesting that older individuals show less decrement in performance on memory tasks that are assumed to involve less cognitive effort, although findings are mixed (see Ward, Berry & Schanks, 2013, for review and discussion). Study 4 was undertaken to examine this issue.…”
Section: Studysupporting
confidence: 85%
“…This claim has been contested by recent modelling efforts that allow for different measurement noise in each type of test820. Importantly, our use of SEM allowed us to address this possibility by modelling test-specific residual variance.…”
Section: Discussionmentioning
confidence: 97%
“…It is widely believed that implicit memory is preserved in normal aging, in contrast to reduced explicit memory (reviewed in Fleischman, 2007; but see Ward, Berry, & Shanks, 2013a, 2013bWard, de Mornay Davies, & Politimou, 2015). It has been suggested that the beneficial use of context information in item recognition involves implicit processes, whereas recall/recognition of target-context associations involves explicit processes.…”
Section: Discussionmentioning
confidence: 99%